ANALISIS KESALAHAN PENGGUNAAN PENGGANTI KATA TANYA â€œZENMEâ€ DAN â€œZENMEYANGâ€ PADA MAHASISWA BAHASA MANDARIN UNTAN - Agustyanti, Devi Nur; Thamrin, Lily; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThere are so many interrogative pronouns in Mandarin Language?including ?zenme?and ?zenmeyang? . These two words are commonly used in daily conversation. Althoughthe two words have the same meaning, but the utilization of these words are distinct. So, asa foreign languange student, understanding the utilization of ?zenme? and ?zenmeyang?are difficult.. The author has done a research based on Tanjungpura University studentsutilization of ?zenme?and ?zenmeyang. Analyzing the misuse of these interrogativepronouns. The result shows that the percentage of Tanjungpura University students thatare using the word ?zenme? and ?zenmeyang? correctly are 71% and 61%, while 29%of?zenme?and 39%of ?zenmeyang?is misused. The mistake that often occur aremisplacing these words in a sentence. Based on that conclusion, the author puts forwardsome teaching suggestions of the issues. Keywords : interrogative pronouns zenme and zenmeyang error analysis